A Common Factors Approach to Supporting University Students Experiencing Psychological Distress. Issue 2 (3rd April 2017) - Surette, Tanya E.; Shier, Micheal L.
ABSTRACT: This study empirically assessed the applicability of the common factors model to students accessing university-based counseling ( n  = 102). Participants rated symptoms of depression, anxiety, and somatization at intake and discharge. Therapists kept detailed session notes on client factors and therapy process variables. Data were analyzed utilizing structural equation modeling to assess what common factors significantly predicted outcome improvements. Authors found duration of therapy, positive life events, and intimate relationship supports positively influenced outcomes. Increases in the number of intervention approaches and sessions negatively influenced certain outcomes. The present findings have important implications for programming and treatment planning within on-campus counseling services.